2008
DOI: 10.1007/s10620-008-0271-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E Polymorphisms in Patients with Non-Alcoholic Steatohepatitis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of abnormal hepatic steatosis in the absence of alcohol abuse worldwide. Non-alcoholic steatohepatitis (NASH) is the most progressive form of NAFLD. The aim of this study was to investigate the role of apolipoprotein E (APOE) polymorphisms in the development of NASH. We analysed 57 NASH patients and 245 healthy controls using a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method in a case-control study. The diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 45 publications
1
40
0
2
Order By: Relevance
“…Elevations in HDL cholesterol levels confer a lower risk of chronic heart disease [16]. Recently, studies examining the pathogenesis of NASH have demonstrated an association of hepatic apolipoprotein synthesis/secretion with the development of steatosis [31,32]. Our study provides evidence that the risk of FL is decreased across the categories of alcohol consumption, despite an increase in serum triglyceride levels.…”
Section: Discussionsupporting
confidence: 54%
“…Elevations in HDL cholesterol levels confer a lower risk of chronic heart disease [16]. Recently, studies examining the pathogenesis of NASH have demonstrated an association of hepatic apolipoprotein synthesis/secretion with the development of steatosis [31,32]. Our study provides evidence that the risk of FL is decreased across the categories of alcohol consumption, despite an increase in serum triglyceride levels.…”
Section: Discussionsupporting
confidence: 54%
“…Sazci et al found VLDL levels significantly higher in NASH patients compared with the healthy controls [18]. These authors also demonstrated an association between VLDL and hypertriglyceridaemia and between apolipoprotein E (APOE) polymorphism and VLDL [18]. The most likely reason for increased VLDL level in NASH patients could be explained based on a previous study by Huang et al [19].…”
Section: Discussionmentioning
confidence: 91%
“…Stored triglycerides in adipose tissue and those newly synthesized within the liver through de novo lipogenesis are the major sources of triglycerides in the liver, and major routes of triglyceride elimination from the liver are fatty acid β-oxidation and the secretion of VLDL [17]. Sazci et al found VLDL levels significantly higher in NASH patients compared with the healthy controls [18]. These authors also demonstrated an association between VLDL and hypertriglyceridaemia and between apolipoprotein E (APOE) polymorphism and VLDL [18].…”
Section: Discussionmentioning
confidence: 98%
“…22,23 LDLR or ApoE single-knockout mice developed some of the NAFLD characteristics [24][25][26] but generally failed to broadly reflect the whole spectrum of NAFLD key features. As such, ApoE À / À mice on a fat-and cholesterol-enriched diet developed hepatic inflammation but only mild steatosis.…”
Section: Discussionmentioning
confidence: 99%